Role of Stem Cells in the Management of Type-I Diabetes Mellitus - Arjun, H. R.; Halagali, Praveen; Tausi, Y. Mohammed; Paramakrishnan, N.; Rakshith, U. R. (Indian Journal of Pharmaceutical Education and Research, 2023)
The paper aims to accent Type-1 DM along with its etiology, pathophysiology, and treatment in this review. Diabetes is considered the chronic ailment of hypoglycemia ensuing from the duo of the dearth of insulin action and secretion of insulin considered as both. Moreover, Type-1 is a result of autoimmune of the cells of islets of the pancreas. The confrontation to the insulin or secretion of insulin lacking due to changes in living standards, habit change, dearth of exercise along with aging also, but one of the most relevant and prevalent reasons is a lifestyle change and also change in food habits along with the stress of the day-to-day life. Stem cell therapy is an expensive treatment and obtaining stem cells also is difficult due to ethical issues and availability is also less. Presently accessible ailment for type-1 is insulin supply therapy but it is also associated with many hitches. Advanced replacements like islets have demonstrated fruitful results in reinstating glucose levels. Moreover, in severe type 1-DMM and it has been delimited due to its high cost, not economic process, shortfall of donors, etc. Replacement of beta-like cells that are obtained from differentiation of human Pluripotent Stem Cells (hPSCs) also exhibited results with flying colors and gained the spotlight, but in stem cell therapy getting beta cells along with complete insulin secretion is decisive.
Keywords: Diabetes Mellitus; Stem cells; Hyperglycemia